Secretory Profile of Selected Gut Bacteria of Cockroaches: A Potential Source of Anti-Infective Agents - Akbar, Noor; Siddiqui, Ruqaiyyah; Abouleish, Mohamed Yehia; Muhammad, Jibran Sualeh; Khan, Naveed Ahmed * (Bentham Science Publishers, 2022)
Pests, such as cockroaches, thrive in polluted conditions that are detrimental to Homo sapiens, suggesting that such species possess mechanisms to protect themselves against pathogens. Besides their immunity to fight pathogens, we hypothesize that the microbial gut flora of pests produces antimicrobials to thwart communicable diseases. It is proposed that the search for new antimicrobials originating from unusual sources will generate useful leads in the identification of new anti-infective agents.